FOREIGN LANGUAGE STUDENTS’ VIEWPOINT ON COMPETENCIES OF TEACHER’S PROFESSION - Kriaučiūnienė, Roma (Acta Paedagogica Vilnensia, 2010)
The article presents an overview of some aspects of the development of future foreign language teachers’ moral attitudes at contemporary universities. It aims to determine the respondents’ viewpoint on teacher’s professional linguistic, professional pedagogical, intercultural and general competencies and to reveal its possible influence on the development of their moral attitudes.The majority of the respondents think that foreign language teachers should firstly acquire professional linguistic, secondly – professional pedagogic, thirdly – intercultural and fourthly – general competence, with its insufficient acknowledgment of its two manifestations related with professional activities to awaken pupils’ positive attitude towards spiritual values and to direct their own lives accordingly. However, correlative analysis revealed the strongest links between the respondents’ views on professional pedagogic and general competencies and the components of moral attitude, the most significant being with the general competence. Such data prove that the respondents’ viewpoint on general competence can have the most favorable influence on moral attitude development.It has been concluded that the respondents lack a wider viewpoint on teachers’ general competence that can determine their ability to take action in unpredictable professional situations. The lack of favorable evaluation of professional pedagogical and general competencies, can limit positive influence on future foreign language teachers’ moral attitude development. Therefore, foreign language teaching process should be more focused on fostering general competence, thus providing more favorable possibilities for the development of future teachers’ moral attitudes.
Keywords: professional linguistic; professional pedagogical; intercultural and general competencies of teachers’ profession; future foreign language teachers; moral attitude